Anti-inflammatory effects of Perillae Herba ethanolic extract against TNF-α/IFN-γ-stimulated human keratinocyte HaCaT cells. (30th January 2018) - Yang, Ju-Hye; Yoo, Jae-Myung; Lee, Esther; Lee, BoHyoung; Cho, Won-Kyung; Park, Kwang-Il; Yeul Ma, Jin
Abstract: Ethnopharmacological relevance: Perillae Herba is a perennial plant that is widely distributed throughout Asia. The leaves of Perillae Herba have been widely used to treat various diseases, such as cold due to wind-cold, headache, cough, abdominal fullness, distention, and fish and crab poisoning. Materials and methods: To assess the anti-inflammatory activity of Perillae Herba leaf ethanolic extract (PHE) in human keratinocytes, we measured the tumor necrosis factor (TNF)-α/interferon (IFN)-γ-induced mRNA expression and production of proinflammatory chemokines such as thymus and activation-regulated chemokines; regulated on activation, normal T cell expressed and secreted; interleukin (IL)-6; and IL-8 in HaCaT cells. We evaluated the ability of PHE to decrease the expression of proinflammatory marker proteins, such as mitogen-activated protein kinase (MAPK), STAT-1, and NK-κB, using western blot analysis and immunocytochemistry. Results: PHE inhibited activation of p38, ERK, and JNK and suppressed the phosphorylation of STAT-1 and NK-κB in TNF-α/IFN-γ-stimulated HaCaT cells. PHE also suppressed chemokine mRNA and protein levels in TNF-α/IFN-γ-stimulated HaCaT cells. PHE appears to regulate chemokine formation by inhibiting activation of MAPK, as well as the STAT-1 and NK-κB pathways. Conclusions: PHE suppresses the expression and production of TNF-α/IFN-γ-stimulated proinflammatory chemokines by blocking NF-κB, STAT-1, and MAPK activation. Graphical abstract: